Instagram @rumahdasi_ as a Promotional Strategy in Building Brand Awareness in 2023-2024 - Pranata, Zeintito; Sovia Sitta Sari (Jogjakarta Communication Conference (JCC), 2024)
This research delves into the pivotal role of building brand awareness and crafting a robust brand image within society through strategic promotion on Instagram, focusing on 'Rumah Dasi,' a tie brand established in 2020 with a physical store on Jalan Iowa. The study identifies challenges in promotional endeavors, marked by stagnant growth with each campaign, aiming to explore Instagram's promotional dynamics and the process of fostering brand creativity. Employing a qualitative descriptive approach by Kotler and Keller's theory, the research underscores the significance of brand recognition and recall in shaping consumer purchasing behavior. The findings illuminate effective Instagram promotion strategies and the underlying principles essential for successful brand cultivation, facilitating broader audience engagement and outreach. A key conclusion drawn is the pivotal role of a communication-centric promotional strategy in augmenting brand awareness and advocating for the integration of brand awareness and Instagram promotion to streamline consumer decision-making processes. Ultimately, the study emphasizes the imperative of incorporating brand creativity into social media platforms, particularly Instagram, as a potent avenue for promotional activities.